2019
DOI: 10.3390/publications7030045
|View full text |Cite
|
Sign up to set email alerts
|

The DOAJ Spring Cleaning 2016 and What Was Removed—Tragic Loss or Good Riddance?

Abstract: In December 2012, DOAJ’s (The Directory of Open Access Journals) parent company, IS4OA, announced they would introduce new criteria for inclusion in DOAJ and that DOAJ would collect vastly more information from journals as part of the accreditation process—journals already included would need to reapply in order to be kept in the registry. My working hypothesis was that the journals removed from DOAJ on May 9th 2016 would chiefly be journals from small publishers (mostly single journal publishers) and that DOA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…In his analysis of journals indexed in DOAJ, he found that almost 90 percent of publishers only publish a single journal, amounting to 55 percent of all journals, while larger publishers with more than 10 journals only constitute 1 percent of publishers but publish 23.3 percent of journals. This distribution has been largely confirmed in a new study [18]. There are challenges for small publishers related to economy, efficiency and expertise.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In his analysis of journals indexed in DOAJ, he found that almost 90 percent of publishers only publish a single journal, amounting to 55 percent of all journals, while larger publishers with more than 10 journals only constitute 1 percent of publishers but publish 23.3 percent of journals. This distribution has been largely confirmed in a new study [18]. There are challenges for small publishers related to economy, efficiency and expertise.…”
Section: Discussionmentioning
confidence: 66%
“…In 2014 DOAJ introduced new criteria for inclusion and required journals that were already registered to reapply before April 2016, in order to be kept in the registry. Looking at journals that were removed from DOAJ after April 2016, Frantsvåg [18] finds that the single journal publishers lost nearly one third of journals while the percentage of lost journals steadily decrease in relation to publishers' size. It is important to note that the removal of journals has little to do with scholarly quality but is primarily a result of failure to reapply.…”
Section: Discussionmentioning
confidence: 99%
“…A decline in the number of American and Indian OA-journals from 2013 to 2017 was due to a significant overhaul of OA-journals in DOAJ at this period (Table 2). Indeed, on May 9, 2016, many sub-standard and predatory OA-journals were removed from DOAJ, though as early as in December 2012, it had been announced that new and more stringent criteria would be introduced for registration of OA-journals in DOAJ (Frantsvåg, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The biggest challenge that the DOAJ likely faced in its history was the apparent listing of unscholarly (possibly "predatory") OAJs. Facing public scrutiny and pressure from scholarly OAJs, publishers and societies, the DOAJ reassessed its indexed members in a thorough process of reaccreditation [4]. The DOAJ is considered by OA scholars to be a premium OAJ whitelist, particularly…”
Section: Introductionmentioning
confidence: 99%